The use of Treatment and Education of Autistic and Related Communication Handicapped Children in schools to improve the ability of children with autism to complete tasks independently: A single‐case meta‐analysis. - Zhou, Kun; Liu, Xinchao; Li, Shuting; Zhang, Yuxin; An, Rui; Ma, Siyue (Child: Care, Health & Development, 2024)
Objective: To investigate the effectiveness of a Treatment and Education of Autistic and Related Communication Handicapped Children (TEACCH) intervention in schools for improving independent task performance in children with autism spectrum disorders (ASD). Methods: We screened relevant studies published up to December 2022 from Web of science, ERIC, PsycINFO and other databases using predefined inclusion/exclusion criteria to identify suitable intervention studies for meta‐analysis. Tau‐U effect sizes were calculated for each A‐B comparison extracted from the included experiments. Moderated analyses were conducted to examine the type of intervention (independent variable), intervention target behaviours (dependent variable), participant characteristics, setting characteristics and intervener characteristics. Results: A total of 14 studies (38 participants) met the criteria and were included in the meta‐analysis. The analysis results showed that TEACCH had a significant intervention effect, and the overall intervention effect size was Tau‐U = 0.85[0.77, 0.91]. There were significant differences in the intervention target behaviour variables (p < 0.01), limited variation in the intervention type variables, but no differences in participant characteristics, setting characteristics and intervenor characteristics. Conclusion: The use of TEACCH is effective in improving independent task completion in children with ASD and provides evidence‐based recommendations for its extended use in schools.